Legal protection of the human genome – excessive or disproportionate? - Plonka-Syroka, Bozena; Stych, Marek (Current Issues in Pharmacy and Medical Sciences, 2025)
Throughout the 20th century, life expectancy in developed countries considerably increased from 40 to 70 years. This stemmed mainly from the technological advancements in medicine that have been taking place since the end of the 19th century. Although the development of contemporary clinical medicine is undoubtedly beneficial to public health, it may also entail certain hazards. Hence, both in international and national law systems one can find legal regulations setting the limits of this development and taking into account the principles of public safety in its contemporary understanding. Both the human being as a whole and the human genome are protected de jure. The article attempts to answer the question whether the currently binding genome regulations are excessive or disproportionate. The authors use the dogmatic-legal and the theoretical-legal methods in the study. The article ends with conclusions.